2006
DOI: 10.1002/cphc.200600261
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties and Photocatalytic Activity of Ptcore/Agshell Nanoparticle‐Loaded TiO2

Abstract: Bimetallic nanoparticles are successfully formed on the surface of TiO2 (see figure) with Ag shell layer (nL) control. Pt@Ag/TiO2 exhibits unique photocatalytic performances for reduction of nitorobenzene at nL≤1, however when nL exceeds ≈1 they are similar to those of Ag/TiO2. Furthermore at the critical value of nL≈1, the surface properties of Pt@Ag nanoparticles change from Pt to Ag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Recently, the successful chemoselective photocatalytic reduction of various nitroaromatic compounds (carrying reducible groups other than NO 2 ) to the corresponding aminobenzenes in the presence of TiO 2 suspended in acetonitrile with oxalic acid acting as a sacrificial reagent was reported. 86 Tada et al 89,90 studied the effect of metal doping of the photocatalyst on the reduction of nitroaromatic compounds. The selectivity of the Ag/TiO 2 -photocatalysed reduction was rationalised on the basis of the selective adsorption of the nitroaromatic compounds on the modified catalyst surfaces and the restriction of the product, that is, aniline from readsorbing.…”
Section: Critical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the successful chemoselective photocatalytic reduction of various nitroaromatic compounds (carrying reducible groups other than NO 2 ) to the corresponding aminobenzenes in the presence of TiO 2 suspended in acetonitrile with oxalic acid acting as a sacrificial reagent was reported. 86 Tada et al 89,90 studied the effect of metal doping of the photocatalyst on the reduction of nitroaromatic compounds. The selectivity of the Ag/TiO 2 -photocatalysed reduction was rationalised on the basis of the selective adsorption of the nitroaromatic compounds on the modified catalyst surfaces and the restriction of the product, that is, aniline from readsorbing.…”
Section: Critical Reviewmentioning
confidence: 99%
“…89,90 This is also useful for reactions other than dehalogenation. Tada et al 89,90 reported an increase in the amount of adsorbed nitrobenzene when using Ag and Pt-Ag/TiO 2 compared to bare TiO 2 , while restricting the product aniline from re-adsorbing. This selective adsorption of nitrobenzene resulted in a considerable increase in the activity and the selectivity of its photocatalytic reduction to aniline.…”
Section: Modifying Photocatalyst Surface Propertiesmentioning
confidence: 99%
“…19 Also, in the Au/TiO 2 -UV catalyzed reactions, the metal shell on the Au core was shown to affect the adsorptivity and the product selectivity. 20,21 On the other hand, Hutchings and co-workers have described in their review paper that alloying of Au NPs with Cu improves the thermocatalytic activity for oxidations of CO, propene, and alcohol, 22 and Shiraishi et al have recently shown that alloying Au NPs with 30% of Cu enhances the activity of the Au/TiO 2 plasmonic photocatalyst for alcohol oxidation. 23 a Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…7. The Au nanoparticles followed by act as reduction sites in presence of oxygen while the holes remaining in the valence band of MnWO 4 can initiate oxidation reactions with OH -or H 2 O at its surface [11]. By this noble metals loading mechanism, photogenerated charge-carriers can be separated efficiently so that noble metal loaded metal tungstates can completely mineralize organic pollutants by utilizing visible light.…”
Section: Resultsmentioning
confidence: 98%
“…It has been reported that loading of a few noble metals like Au, Ag, Pt, Pd on to single-phase or composite photocatalyst systems is known as one of the successful methods for the improvement of photocatlytic redox reactions. The role of loaded metals is trapping and subsequent transfer of photoexcited electrons on the principal photocatalyst surface where the photocatalytic reduction reaction occurs and the photocatalytic efficiency has been greatly improved [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%